2014
DOI: 10.2903/j.efsa.2014.3770
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on applications (EFSA-GMO-UK-2008-57 and EFSA-GMO-RX-MON15985) for the placing on the market of insect-resistant genetically modified cotton MON 15985 for food and feed uses, import and processing, and for the renewal of authorisation o

Abstract: Cotton MON 15985 was developed by biolistic transformation of cotton MON 531 to express Cry2Ab2 and GUS in addition to the Cry1Ac and NPTII proteins. Cry proteins in MON 15985 confer resistance to major lepidopteran cotton pests, whereas the GUS and NPTII proteins were used as markers during product development. Molecular characterisation of MON 15985 did not give rise to safety issues. The EFSA GMO Panel could not conclude on the potential occurrence of unintended effects for agronomic and phenotypic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…For cotton events GHB614 and LLCotton25, the GMO Panel concluded that there is no increased likelihood for HGT; for cotton event MON 15985, the GMO Panel concluded that there is increased likelihood of transfer of the antibiotic resistance gene nptII, but that MON 15985 material is highly unlikely to contribute to the environmental prevalence of this gene. No adverse effects on human and animal health and the environment are expected (EFSA, 2006b(EFSA, , 2009aEFSA GMO Panel, 2014a). New bioinformatic data 38 confirmed the previous conclusions.…”
Section: Plant-to-microorganism Gene Transfersupporting
confidence: 59%
See 1 more Smart Citation
“…For cotton events GHB614 and LLCotton25, the GMO Panel concluded that there is no increased likelihood for HGT; for cotton event MON 15985, the GMO Panel concluded that there is increased likelihood of transfer of the antibiotic resistance gene nptII, but that MON 15985 material is highly unlikely to contribute to the environmental prevalence of this gene. No adverse effects on human and animal health and the environment are expected (EFSA, 2006b(EFSA, , 2009aEFSA GMO Panel, 2014a). New bioinformatic data 38 confirmed the previous conclusions.…”
Section: Plant-to-microorganism Gene Transfersupporting
confidence: 59%
“…This gene was only used as a selectable marker during the development of MON 15985. This gene is under the control of a prokaryotic promoter and it is therefore not expressed in parental line cotton MON 15985 (EFSA GMO Panel, 2011c, 2014a. (Lebrun et al, 2003) The amino acid sequence of the maize EPSPS enzyme was modified by two substitutions to render it tolerant to glyphosate.…”
Section: Genetic Elements and Biological Functions Of The Insertsmentioning
confidence: 99%
“…Feeding Studies Various forms of cottonseed (ground whole seed, whole flour, and processed meal) have been incorporated into diets and fed to rats at different incorporation rates. In a 90-day rat feeding study performed with ground whole cottonseed and reviewed in an EFSA Scientific Opinion [39], groups of 20 Sprague Dawley rats were fed diets containing 2 or 5 percent (w/w) ground GM cottonseed. Six additional groups were fed diets containing 5 percent (w/w) ground cottonseed from commercial non-GM cotton varieties.…”
Section: Dietary Considerations For Cottonseed In 90-day Ratmentioning
confidence: 99%